Peninggalan Kesultanan Singgora sebagai Warisan Ketamadunan Melayu-Islam di Songkhla, Thailand Selatan : Remains of the Singora Sultanate as Heritage of Malay-Muslim Civilization in Songkhla, Southern Thailand - Welani, Irna; Nazaruddin, Dony Adriansyah (Journal of Al-Tamaddun, 2023)
The city of Songkhla in Southern Thailand was originally from a Malay-Muslim kingdom called the Sultanate of Singora Darussalam. This sultanate was located in the Khao Daeng hilly area in the present Singhanakhon area. The city which was previously named Singora was founded in the early 17th Century by a Persian merchant named Dato Mogol (or Datuk Mughal, also known as Datuk Muzaffar) who later ruled Singgora under the name of Sultan Muzaffar Shah. His death caused this sultanate to be continued by his son, Sultan Sulayman Shah, who succeeded in bringing Singora to its glory. After his death, he was replaced by his son named Sultan Mustapha Shah. The prolonged conflict of the late 17th Century led to the collapse of this kingdom. However, it is still difficult to find detailed and up-to-date references to this sultanate and its legacy. Therefore, this study aims to reveal the history of the Sultanate of Singora and its legacy as the heritage of a Malay-Muslim history of civilization in Songkhla. Data and information for this study were obtained through literature review, field study, discussion and interviews with related institutions and local communities. The results of this study show that the Sultanate of Singora once ruled for 75 years (1605-1680) in this area based on evidence of historical sites such as the tomb of Sultan Sulayman Shah and his family, a city wall, a network of forts, and a moat. It is hoped that Songkhla’s heritage can be preserved as archaeological sites because indeed it can uncover the history of the Malay-Muslim civilization in Songkhla for present and future generations.